ANALISIS PEMBERIAN INSENTIF TERHADAP KINERJA KARYAWAN (Studi kasus pada PT. Pusri Palembang departemen operasi amonia 1B) - Mario, Asma; Ramadhany, Putra (Fakultas Ekonomi Universitas IBA, 2019)
This study aims to determine and analyze the effect of incentives on employee performance in the ammonia operations department 1 B PT. Pupuk Sriwijaya Palembang. This research was conducted at PT. Pupuk Sriwijaya Palembang with a research sample of 55 employees in the ammonia operation section 1 B PT. Pupuk Sriwijaya Palembang. The sampling method uses saturated sampling where the entire population is used as the research sample. Data retrieval of this research was conducted at the Department of Manpower PT. Pupuk Sriwijaya Palembang. The results of quantitative research show the magnitude of the effect of training on the performance of employees of the ammonia operations department 1 B PT. Pupuk Sriwijaya Palembang amounted to 20.2% and the remaining 79.8% explained other factors outside the variables studied in this study, including ability and expertise, knowledge, work design, personality, work motivation, leadership, leadership style, organizational culture, work environment, job satisfaction, loyalty, commitment and work discipline, also affect the performance of employees of the ammonia operations department 1 B PT. Pupuk Sriwijaya Palembang.